A Closer Look At The Akan Determiner Bi: An Epistemic Indefinite Analysis - Owusu, Augustina Pokua (My University, 2019)
This study aims to shed light on the epistemic indefinite interpretation (EI) of the Akan (Asante Twi) determiner bi which hitherto had not been discussed in the Akan literature. In previous studies, Amfo (2010) and Arkoh (2011) review its referential or specific indefinite interpretation. The current study shows that in addition to the above interpretation when bi is used, the speaker signals that she does not have access to all the information about who or what satisfies the existential claim they are making. I employ Aloni (2001) and Aloni & Port’s (2015) theory of conceptual covers and methods of identification to determine “knowledge” of a referent in a particular context. Conceptual covers are sets of individual concepts which exclusively and exhaustively covers the domain of individuals (Aloni 2001). I show that the epistemic indefinite analysis and the specificity or referential analysis are compatible. When bi is used, the speaker asserts she can name a noteworthy or identifying property about the referent of the NP, which is the referential or specificity interpretation. Additionally, she presupposes that she is ignorant about further characterizing information about the referent, the epistemic indefinite interpretation.
Keywords: Akan determiner; indefinite analysis; Akan literature